A stereoselective and flexible synthesis to access both enantiomers of N-acetylgalactosamine and peracetylated N-acetylidosamine - Riedl, Bettina; Schmid, Walther (Beilstein Journal of Organic Chemistry, 2018)
Synthetic approaches towards N-acetylgalactosamine (GalNAc) have been attracting considerable interest since this compound is known for its pivotal role in cell–cell interaction and receptor induced cell signaling. Herein, we present a synthetic route in which two of the four stereogenic centers present in the target compound are derived from enantiopure tartaric acid being selectively converted to epoxy alcohols. The key step is the Pd-catalyzed, stereo- and regioselective epoxide opening and subsequent nucleophilic substitution of an azide functionality. This approach enables the synthesis of the naturally D- and unnaturally L-configured GalNAc, as well as both enantiomers of the largely unknown N-acetylidosamine (IdoNAc).
Keywords: asymmetric synthesis; carbohydrates; N-acetylgalactosamine; N-acetylidosamine